Evaluating the efficiency of financial resource transformation into ESG performance: a DEA application in the german industry - Vasconcelos, Mateus Vilela Peloso; Cunha, Ícaro Guilherme Félix da; Paiva, Cecilia Loretti; Roiz, Guilherme Augusto; Rebelatto, Daisy Aparecida do Nascimento (Brazilian Journal of Operations & Production Management, 2025)
Purpose: To evaluate the efficiency of transforming financial resources into environmental, social, and governance (ESG) results by German companies in the Industrial Machinery and Equipment sector from 2018 to 2022 through Data Envelopment Analysis (DEA) application. Design/methodology/approach: This study applies DEA to assess the efficiency of companies in the M&E sector, using data from the Refinitiv platform for the 2018–2022 period. The analysis is framed in the resource-based view (RBV) theory and incorporates qualitative benchmarking through Porter’s Five Forces framework. Findings: Nordex SE and SGL Carbon SE emerged as ESG efficiency benchmarks despite financial constraints, while Siemens AG stood out as a sectoral reference due to its market leadership, consistent performance, and strong integration of sustainability into corporate strategy. Research limitations/implications: The study is limited by its five-year scope, which includes the Covid-19 pandemic period, and by its focus solely on German companies, potentially limiting broader applicability. Practical implications: The study identifies practices and performance patterns among leading firms that can inform ESG-related decision-making in the industrial machinery and equipment sector. Originality/value: This study introduces a novel approach by combining DEA alongside qualitative analyses to benchmark and assess ESG-driven competitive advantages, offering an innovative perspective on the effective allocation of financial resources toward ESG objectives in the M&E sector.